Global trends and frontiers in research on exercise training for heart failure: a bibliometric analysis from 2002 to 2022 - Yang, Zhen; Zhong, Zi-Yi; Zhao, Cong-Na; Yin, Ming-Yue; Wang, Jia-Hui; Wei, Jing; Wen, Zhi-Shen; Qi, Ming (Frontiers in Cardiovascular Medicine, 2023)
Background Heart failure is a common cardiovascular disease that imposes a heavy clinical and economic burden worldwide. Previous research and guidelines have supported exercise training as a safe, effective, and cost-efficient treatment to intervene in heart failure. The aim of this study was to analyze the global published literature in the field of exercise training for heart failure from 2002 to 2022, and to identify hot spots and frontiers within this research field. Methods Bibliometric information on literature on the topic of exercise training for heart failure published between 2002 and 2022 was searched and collected in the Web of Science Core Collection. CiteSpace 6.1.R6 (Basic) and VOSviewer (1.6.18) were applied to perform bibliometric and knowledge mapping visualization analyses. Results A total of 2017 documents were retrieved, with an upward-stable trend in the field of exercise training for heart failure. The US authors were in the first place with 667 documents (33.07%), followed by Brazilian authors (248, 12.30%) and Italian authors (182, 9.02%). The Universidade de São Paulo in Brazil was the institution with the highest number of publications (130, 6.45%). The top 5 active authors were all from the USA, with Christopher Michael O'Connor and William Erle Kraus publishing the most documents (51, 2.53%). The International Journal of Cardiology (83, 4.12%) and the Journal of Applied Physiology (78, 3.87%) were the two most popular journals, while Cardiac Cardiovascular Systems (983, 48.74%) and Physiology (299, 14.82%) were the two most popular categories. Based on the results of keyword co-occurrence network and co-cited reference network, the hot spots and frontiers of research in the field of exercise training for heart failure were high-intensity interval training, behaviour therapy, heart failure with preserved ejection fraction, and systematic reviews. Conclusion The field of exercise training for heart failure has experienced two decades of steady and rapid development, and the findings of this bibliometric analysis provide ideas and references for relevant stakeholders such as subsequent researchers for further exploration.